In utero and Lactational Exposure to Acetamiprid Induces Abnormalities in Socio-Sexual and Anxiety-Related Behaviors of Male Mice - Sano, Kazuhiro; Isobe, Tomohiko; Yang, Jiaxin; Win-Shwe, Tin-Tin; Yoshikane, Mitsuha; Nakayama, Shoji F.; Kawashima, Takaharu; Suzuki, Go; Hashimoto, Shunji; Nohara, Keiko; Tohyama, Chiharu; Maekawa, Fumihiko (Frontiers in Neuroscience, 2016)
Neonicotinoid, a widely-used pesticide group designed to selectively bind to insect nicotinic acetylcholine receptors, were considered to be relatively safe for mammalian species. However, it has been found to activate vertebrate nicotinic acetylcholine receptors than ever anticipated, and could be toxic to the mammalian brain. In the present study, we evaluated the developmental neurotoxicity of acetamiprid (ACE), one of the most-widely used neonicotinoid, in C57BL/6J mice whose mothers were administered ACE via gavage at doses of either 0 mg/kg (control), 1.0 mg/kg (low-dose) or 10.0 mg/kg (high-dose) from gestational day 6 to lactation day 21. As possible endpoints, a battery of behavior tests, socio-sexual and anxiety-related behaviors, as well as testosterone level and the number of vasopressin-immunoreactive cells in the paraventricular nucleus of the hypothalamus were examined. In addition, behavioral flexibility was assessed for mice in a group-housed environment using an IntelliCage, a fully automated mouse behavioral analysis system. In adult male mice exposed to ACE at both low and high doses, significant reduction of anxiety level was found in the light-dark transition test. Males in the low-dose group also showed a significant increase in sexual and aggressive behaviors. In contrast, neither the anxiety nor the sexual behavior of females was altered. No impairments in testosterone level, the number of vasopressin-immunoreactive cells, and behavioral flexibility were detected in either sex. These results suggest the possibility that in utero and lactational ACE exposure interferes with the development of the neural circuits required for executing socio-sexual and anxiety-related behaviors in male mice specifically.